Exposure to Batrachochytrium dendrobatidis metabolites altered ghost shrimp behavior and reduced mortality - Parker-Athill,Ellisa Carla; Muldro,Liam C.; Malinias,Aiza J.; McMahon,Taegan A. (PeerJ, 2025)
Batrachochytrium dendrobatidis, or Bd, is a waterborne, pathogenic chytrid fungus implicated in the decline and extinction of hundreds of amphibian species worldwide. Bd can infect multiple taxa, causing disease in susceptible species associated with epidermal degradation, lethargy, weight loss, gill damage, and disruption of osmoregulation and cardiac dysfunction, ultimately leading to mortality in many instances. Bd produces water soluble chemicals (Bd metabolites) that, while implicated in infection and Bd-related pathology, have also been shown to have prophylactic effects for amphibians. This study examined the impact of Bd metabolite exposure on critical non-target freshwater invertebrates to better understand how Bd metabolites might impact non-target species if used as a prophylaxis in the field. We examined the effects of Bd metabolites on the freshwater species, Palaemonetes paludosus, or ghost shrimp, focusing specifically on the effects on behavior, cardiac function, and mortality. Shrimp were randomly split into two treatment groups and on day 4, they were dosed with 1 ml of either an artificial spring water (ASW) control or Bd metabolite treatment. We found that ghost shrimp exposed to Bd metabolites experienced decreased heart rate, reduced threat response behaviors, and reduced mortality, when compared to those exposed to an ASW control. Our findings suggest that exposure to the Bd metabolites may actually provide some benefits to ghost shrimp as it decreased mortality compared to controls. While more research is needed to understand if there are indirect impacts of the metabolites associated with the behavioral and cardiac changes, this research highlights that exposure to Bd metabolites does not appear to be detrimental to these critical, keystone freshwater invertebrates. This is particularly important given that Bd metabolites may be used prophylactically in the field, which may lead to non-target organism exposure.
Keywords: Batrachochytrium dendrobatidis; Ghost shrimp; Fungus; Vaccine; Prophylaxis; Chytrid fungus; Behavioral ecology; Freshwater invertebrates; Palaemonetes paludosus